Analisis Tingkat Pemahaman Siswa Sekolah Menengah Atas Negeri 7 Seram Bagian Barat terhadap Kedudukan Pancasila Sebagai Falsafah Negara - Ismunandar Payapo; Lisye Salamor; Fatima Sialana (Departement of Mathematics Education, 2023)
Pancasila is a, the basis of the State (NKRI) in which there is a Jimisk Pancasila was formulated as the basis of the State after a long debate by the panding fathers at the BPUPKI session on June 1, 1945, and on August 18, 1945 tanzeal the 1945 Constitution was passed, including the preamble to the 1945 Constitution, Pancasila was taken from traditional values ​​and cultural values. and religious values ​​contained in the outlook of life of the Indonesian people. In other words, the elements contained in Pancasila come from the views of the Indonesian people themselves. Today, students as the next generation of the nation should be able to understand the meaning contained in the art of Pancasila, Panela An understanding of the values ​​contained in Pancasila is very necessary as a reflection of the life of the Indonesian people. Pancasila as the philosophy of the State is very necessary in life, as a nation and as a state, so that we always practice or implement the values ​​of Pancasila in our lives as citizens of a Satar State.has permanently become an inseparable part of the life of the Indonesian Nation Unnik that we as the next generation of the Nation must be able to maintain these values,